Between affection and control: Chinese migrant mothers’ motherhood practices based on the mediated one-dimensional visibility of home cameras - Yunhong, Lyu; Syed Zainudin, Sharifah Sofiah; Boon Sim, Ng (SAGE Publications, 2025)
Home surveillance cameras provide new ways for Chinese migrant mothers to provide such care. Existing research on migrant women’s motherhood focuses mainly on two-way communication technologies represented by mobile text messages and phone calls, without discussing individual surveillance technologies and their compatibility and contradictions with long-distance motherhood. This study will define visibility based on home cameras as mediated one-dimensional visibility and ask what role home cameras, as a surveillance technology, have played in the remote performance of mothering by female migrant workers in China and what kind of mothering practices they have given rise to. The findings show that the one-dimensional visibility provided by home cameras alleviates the anxieties of migrant mothers regarding the lack of intimacy and supervised education due to the features of being able to watch at any time without having to answer and secretive gazing. With this one-dimensional visibility, migrant mothers can watch their children from a distance and provide behavioral interventions and control. However, these interventions can both promote and diminish intimacy. When the two are in conflict, migrant mothers prioritize maintaining intimate relationships, which can have an impact on their children’s growth. This enriches our understanding of mediated motherhood.